Dissemination of Economic Literacy to PGRI 4 Padang High School Students in the Era of Society 5.0 - Dessyta Gumanti; Reni Respita (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The primary objective of the activity is to socialize economic literacy for students at Senior High School SMA PGRI 4 Padang as they face the era of the Industrial Revolution 4.0 so that they can make informed decisions about the various options available, particularly in economic activities in everyday life. To increase economic literacy, direct observation, interviews, and questions and answers were used, as well as socialization through lectures or presentations, training, and simulations. The outcomes of these activities include providing participants with knowledge about the application of economic literacy in making economic decisions in daily life.